3PC-036 Centralised and personalised preparation of intravenous ketamine for patients with resistant depression. Issue 1 (23rd March 2023) - Costa Ching, F; Santos, AR; Castro, S; Barata, M; Marques, E
Abstract : Background and Importance: Depression is the third leading cause of disability in the world and about 1/3 of depressive disorders have resistance to successive treatments. Intravenous infusion of off-label ketamine in subanaesthetic doses has favourable therapeutic responses in a relatively short evaluation time. Accumulated safety evidence is considered an added value in the therapeutic arsenal to treat this pathology. Safety issues of the use of central anaesthetics without the support of anaesthesiology are a pivotal drive for implementing a clinical protocol that includes the pharmacy. The use of fixed dilutions and rhythms of administration as well as personalised centralised preparation in the pharmacy overcomes most concerns about the regular and safe use of this approach on resistant depression. Aim and Objectives: Evaluate the implemented circuit, characterisation of the population and analysis of the impact on the effectiveness and safety of ketamine in resistant depression. Material and Methods: A 19-month retrospective analysis was made on the use of ketamine in patients with resistant depression. The pharmaceutical services database and the Soarian Clinicals® programme were used to collect information and to consult the electronic clinical process of patients that used this therapeutic approach. Results: Indication for ketamine treatment, in addition to the absence of contraindications, means that the patient is not responsive to at least three antidepressants SNRIs and a tricyclic, a potentiation strategies and a score ≥ 9 in the Patient Health Questionnaire-9 (PHQ-9) . The data collected correspond to the period between 01/2021 and 07/2022 and are summarised in table 1 . All cases reported psychopathological improvement recognised by themselves as well as by assistant psychiatrists. Conclusion and Relevance: Ketamine has shown to be a safe alternative provided that local strategies are created to ensure the implementation of criteria in patient selection, preparation, administration, and follow-up protocols. The acceptance and short-term recognition of the benefit of the treatment by patients and professionals allow for achieving the goal of clinical discharge. References and/or Acknowledgements: 1. CORRIGER A. (2022) Ketamine and depression: a narrative review. Conflict of Interest: No conflict of interest